Development of rain attenuation model for Southeast Asia equatorial climate. Issue 10 (1st July 2013) - Nalinggam, Renuka; Ismail, Widad; Jit Singh, Mandeep; Islam, Mohammad Tariqul; Menon, P. Susthitha
Abstract : Statistical distribution of rain attenuation is essential for development of microwave and millimeter‐wave communication links. Therefore rain‐related statistics are very important for a commercialisation system designer. This study proposes modifications to the International Telecommunication Union (ITU‐R P.618‐10) model and an appropriate rain attenuation prediction model for tropical countries. The model was developed based on data obtained from tropical and equatorial regions. The proposed model uses rainfall rate and rain attenuation at 0.01% of the time, R 0.01 and A 0.01, elevation angle θ and altitude of site h s, respectively, as input parameters. The proposed model showed remarkable agreement with existing rain attenuation measured data in terms of prediction errors for mean square, standard deviation and root‐mean square. The proposed rain attenuation model was used for validation by comparing the model with measured data collected from Nigeria, Kenya and Papua New Guinea, whereby the proposed model gave a percentage error below 12%.